Results from a Prospective Observational Study of Men with Premature Ejaculation Treated with Dapoxetine or Alternative Care: The PAUSE Study - Mirone, Vincenzo; Arcaniolo, Davide; Rivas, David; Bull, Scott; Aquilina, Joseph W.; Verze, Paolo (European urology, 2014)
Dapoxetine hydrochloride is a selective serotonin reuptake inhibitor and the first drug approved for the on-demand treatment of premature ejaculation (PE). Its safety was established in a thorough clinical development program. To characterize the safety profile of dapoxetine in PE treatment and to report the incidence, severity, and type of adverse events. We conducted a 12-wk, open-label, observational study with a 4-wk, postobservational contact. A total of 10 028 patients were enrolled, with 6712 patients (67.6%) treated with dapoxetine 30–60mg (group A)and 3316 (32.4%) treated with alternative care/nondapoxetine (group B). Treatment with dapoxetine or alternative care/nondapoxetine. Treatment-emergent adverse events (TEAEs) and concomitant therapy use during the 12-wk observational and the postobservational period were reported. The mean age for all patients was 40.5 yr. In group A, 93.0% of the patients were initially prescribed dapoxetine 30mg. Treatment options for group B patients included clomipramine, paroxetine, fluoxetine, sertraline, topical drugs, condoms, and behavioral counseling. Both treatment regimens were well tolerated. TEAEs were reported by 12.0% and 8.9% of group A and group B, respectively, with the highest incidence observed in patients aged >65 yr for group A (21.4%) and 30–39 yr (9.8%) for group B. The most commonly reported TEAEs were nausea, headache, and vertigo, with a higher incidence in group A (3.1%, 2.6%, and 1.0%, respectively) than in group B (oral drugs: 2.3%, 1.3%, and 0.9%, respectively). There were no cases of syncope in group A and one case in group B. A major limitation is that this was a nonrandomized, open-label, short-term study lacking efficacy data. The results of this postmarketing observational study demonstrated that dapoxetine for treatment of PE has a good safety profile and low prevalence of TEAEs. Syncope and major cardiovascular adverse events were not reported. The high level of adherence by healthcare providers to the contraindications, special warnings, and precautions for dapoxetine minimizes the risk for its use in routine clinical practice. The current risk minimization measures for its identified and potential risks are effective. Dapoxetine is safe when used in routine clinical practice, with a minimum risk of relevant side effects when prescribed according to product labeling. The incidence of treatment-emergent adverse events in this large observational study was lower than that observed during the clinical development of the drug.